Wanprestasi dalam Perjanjian Pre-order pada Transaksi E-Commerce: (Dalam Perspektif Hukum Perikatan) - Aneza Putri Setiadi; Devi Raisa Fauziah; Rosmatun Aliyah; Shintia Purnama Dewi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2026)
The rapid development of digital technology has facilitated the growth of e-commerce, enabling consumers and business actors to conduct transactions more easily and practically. One of the developments in e-commerce is the pre-order system, which allows consumers to place orders for goods that are not yet available but are guaranteed to be delivered once they become available within a certain period based on agreement and product availability. Linguistically, “pre” means before and “order” means request, so pre-order refers to ordering goods prior to their release or during scarcity. Although pre-order systems provide convenience, they also create legal risks such as delayed delivery, price changes, non-conformity of goods with agreements, and unilateral cancellations, which indicate the potential occurrence of breach of contract. This research analyzes breach of contract in pre-order transactions based on Article 1238 of the Indonesian Civil Code (KUHPerdata) and other relevant provisions concerning consumer protection and contractual obligations. The objective of this study is to identify the legal position and binding force of pre-order agreements in e-commerce transactions and to examine legal remedies when a breach of contract occurs. This study employs a normative juridical method. The findings show that pre-order transactions have legally binding force as long as they fulfill the requirements of a valid agreement. However, in practice, many consumers and business actors experience losses due to breaches of contract committed by one of the parties involved.